Restrukturisasi Pembiayaan Bermasalah pada Perbankan Syariah di Masa Pandemi Covid-19: Perspektif Fatwa MUI dan POJK - Faizi; Satrio Adiputro (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2023)
The current restructuring has been extended until 2023 due to micro, small and medium businesses are still affected by Covid-19. This study aims to find out and analyze the application of BTN Syariah KCS Pasar Minggu regarding the restructuring of troubled financing on mortgage products based on POJK number 11/POJK.03/2020, POJK Number 48/POJK.03/2020, POJK Number 17/POJK .03/2021 and DSN MUI Fatwa Number. 48/DSN-MUI/II/2005. This study uses a descriptive qualitative research method. with the subjects taken were Unit Head Collection, Staff Collection and Customers. This study used primary and secondary data sources with interviews, observation, and documentation data collection techniques. The results of this study indicate that the restructuring policy made by the OJK helps improve the economy in Indonesia with customers who can extend payment terms from the bank so that they can fulfil their payment obligations at a predetermined time. In addition, the restructuring provisions stipulated by the DSN MUI are implemented very well and reflect sharia financial practices that align with the main objective of sharia (Maqashid al-shariah) and strengthen the national economy.